Effect of probiotic supplementation on total lactobacilli, bifidobacteria and short chain fatty acids in 2–5-year-old children. (1st January 2017) - Hemalatha, R.; Ouwehand, A. C.; Saarinen, M. T.; Prasad, U. V.; Swetha, K.; Bhaskar, V.
ABSTRACT: ​Background : Consumption of Lactobacillus paracasei Lpc-37 or Bifidobacterium lactis HN019 by 2–5-year-old children was found to reduce risk for diarrhoea and fever during the rainy season. Objective : Can changes in faecal short chain fatty acids (SCFAs) or branched chain fatty acids (BCFAs) explain the observed positive influence of probiotics and their role on nutritional status and diarrhoea risk? Design : Faecal samples were analysed for SCFAs and BCFAs and correlated to Bifidobacterium and Lactobacillus levels; both at the start and after nine months' consumption of either of the two probiotic strains, or placebo. Results : No differences in SCFAs, BCFAs, Lactobacillus or Bifidobacterium levels were found between boys and girls. Severely underweight children were observed to have the highest Lactobacillus levels. Probiotic intervention was found to be associated with higher levels of selected SCFAs and BCFAs in subjects who had experienced diarrhoea. Treatment with either of the probiotics led to changes in SCFAs and BCFAs. SCFAs, acetate, propionate and butyrate, were found to correlate with each other. Likewise, BCFAs isobutyrate, 2-methylbutyrate and isovalerate correlated with each other. After the intervention, L. paracasei Lpc-37 correlated positively with total Bifidobacterium counts and isovalerate levels. B. lactis HN019 counts were found to correlate positively with total bacterial counts and negatively with propionate levels. Conclusions : ​Nutritional status was associated with higher levels of faecal lactobacilli; the meaning of this requires further investigation. The intervention with the two probiotics was observed to influence the levels of faecal SCFAs and BCFAs and there is a differential response in those who developed diarrhoea and those who did not. It is, however, not clear to what extent this is a mechanism that explains the earlier observed effect the strains had on diarrhoea risk.